Izobraževalna moč splošnih knjižnic - Novljan, Silva (Knjižnica, 2004)
Education services also define the activities of Slovene public libraries. Inplanning targeted services they are often faced with development lagging. The accelerated progress in this field also reminds them of their lagging and points to a very uneven development and quality level of library activities inthe various environments they are centered in. Perhaps due to such conditions public libraries do not excell in developing activities to satisfy education needs of their users. Even so, some successful cases point to the fact that libraries know how to act and could be successful under suitable conditions. The article presents an overview on how the law-defined needs for liferlong education (learning), education of users and information literacy, are meet through aquisition policies and through the realisation of different events taking into account the various levels of literacy of the participating population. The analysis of available reports and data point to the fact that libraries could be more successful if supported by increased expert help backed by financial aid.
Keywords: splošne knjižnice; informacijska pismenost; bralna kultura; Lifelong learning; vseživljenjsko učenje